Efek Kemampuan Usaha, Kompetensi Berwirausaha dan Kapabilitas Digital terhadap Pengembangan Usaha Bakery di Banyuwangi - Nurhanafiyah, Anis; Santoso, Budi; Puspitadewi S, Ira (Lembaga Pengembangan Kinerja Dosen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in national economic development, including in the rapidly growing bakery sector in Banyuwangi Regency. However, in facing increasingly intense competition, many business actors continue to encounter challenges such as weak managerial capacity, low entrepreneurial competence, and suboptimal utilization of digital technology. This study aims to analyze the influence of business capability, entrepreneurial competence, and digital capability on the development of bakery businesses in Banyuwangi Regency. The research employed a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to 115 bakery business owners located in three districts Bangorejo, Jajag, and Purwoharjo using the total sampling technique. Data analysis was conducted using multiple linear regression with SPSS version 20. The results show that business capability and entrepreneurial competence have a significant effect on bakery business development, while digital capability does not show a significant influence. These findings highlight the importance of strengthening managerial and entrepreneurial aspects in enhancing the competitiveness of bakery MSMEs, as well as the need for strategic assistance to optimize the integrated use of digital technology. This research provides implications for business actors, training institutions, and local governments in formulating more effective and sustainable MSME empowerment programs and policies.